Living with Companions: On the Peaceful Coexistence of Humans and Other Animals (KULT_online, 2019)
As a burgeoning research field, human-animal studies has extended into nearly all academic disciplines in the past few decades. The anthology published in the Oxford Handbook series in 2017 provides a nuanced while at the same time extensive overview of many of these recent endeavors. Five thematic sub-sections, including 30 individual contributions, compiled by animal studies authority Linda Kalof illustrate an array of paths to follow when attempting to answer questions about human-animal relations. Experts from diverse disciplines offer introductions and comprehensive bibliographies on specific research circling around animal ethics, agency, exploitation, ecosystems, and cultural representations, while conveying both overarching consensus as well as dissonance within the field. The handbook’s only shortcoming is its slim section on animals in cultural representations, especially in terms of literature and other media.